IL-7-Treated Periodontal Ligament Cells Regulate Local Immune Homeostasis by Modulating Treg/Th17 Cell Polarization - Yu, Xin-Yi; Zhang, Zhao-Qiang; Huang, Jia-Chang; Lin, Jia-Yu; Cai, Xue-Pei; Liu, Chu-Feng (Frontiers in Medicine, 2022)
We aimed to investigate the effect of IL-7 on differentiation of CD4+T cells into Treg/Th17 cells through human periodontal ligament cells (hPDLCs) and implications on the immunomodulatory properties of periodontal tissues. The hPDLCs were treated with different concentrations of rhIL-7 for 24 h. Gamma-secretase inhibitor (DAPT) were used to suppresses the activation of Notch 1 signaling. The proliferation, apoptosis, and necrosis were determined using the Cell Counting Kit-8 and flow cytometry. The expression of TGF-β and IL-6 in supernatant were determined by enzyme linked immunosorbent assay. The mRNA levels and protein expression of various target factors were determined by real-time PCR and Western Blot. Flow cytometry was used to detect the mean fluorescence intensity of PD-L1 in hPDLCs and to analyse the differentiation of Treg/Th17 cells. IL-7 promoted proliferation and inhibited apoptosis in hPDLCs, promoted the expression of TGF-β, PD-L1, Notch1, and Jagged1, and inhibited the levels of HIF-1α and TCF7, whereas the addition of DAPT effectively reversed these effects. IL-7 promoted the polarisation of CD4+T cells into Treg cells, but had no significant effect on the differentiation of Th17 cells. Treatment of hPDLCs with IL-7 can promote the polarisation of CD4+T cells into Treg cells by modulating the expression of inflammatory factors and signalling molecules through the Notch1 signalling pathway.